Fasting plasma glucose outperformed 1-hour plasma glucose in predicting diabetes incidence in individuals with family history of young-onset type 2 diabetes - Juliana C N Chan; Ronald Ching Wan Ma; Alice Pik Shan Kong; Baoqi Fan; Eric S H Lau; Elaine Chow; Chun Kwan O; Andrea Luk; Jane PY Ho; Gary TC Ko; Juliana NM Lui (BMJ Open Diabetes Research & Care)
Introduction Family history (FmH) of young-onset type 2 diabetes (YOD) and 1-hour plasma glucose (PG) during the 75-g oral glucose tolerance test predicts incident diabetes, although their interactions remain unknown.Research design and methods In a workforce cohort established in 1998–2003, we ascertained their glycemic status in 2012–2014. We examined the interaction between FmH-YOD and 1-hour PG in predicting diabetes and used receiver operating characteristics (ROC) analysis to compare the performance of 1-hour PG in participants with or without FmH-YOD.Results Among 583 participants (median age (IQR)=41 (36–47) years, 43.7% men, body mass index=23.3 (21.2–26) kg/m2, 40.3% (n=235) had FmH-YOD, 1-hour PG=8.1 (6.4–10.1) mmol/L), 99 (17%) had developed diabetes at a follow-up of 12.1 (11.3–13.1) years. In the FmH-YOD group, 45% in the high 1-hour PG group and 17% in the normal 1-hour PG group developed diabetes. The respective figures were 16% and 1.8% in the FmH-NONE group. Both FmH-YOD and 1-hour PG predicted diabetes with a negative interaction between FmH-YOD and 1-hour PG (OR 0.72, 95% CI 0.55 to 0.93, p=0.013). Compared with (FmH-NONE/normal 1-hour PG) group, the ORs of incident diabetes in (FmH-NONE/high 1-hour PG), (FmH-YOD/normal 1-hour PG), (FmH-YOD/high 1-hour PG) groups were 7.4 (95% CI 1.6 to 35.1, p=0.011), 18 (95% CI 3.3 to 98.1, p=0.001) and 28.2 (95% CI 5.5 to 145.9, p<0.001), respectively. In ROC analysis, the C-statistics of 1-hour PG dropped from 0.83 (95% CI 0.76 to 0.90, p<0.001) in the FmH-NONE group to 0.69 (95% CI 0.62 to 0.76, p<0.001) in the FmH-YOD group (difference=0.14 (95% CI 0.04–0.24), p=0.006) where fasting PG (FPG) was the best predictor (0.792 (95% CI 0.730–0.853), p<0.001).Conclusions FPG outperformed 1-hour PG in predicting incident diabetes in people with FmH-YOD, calling for precise classification and preventive strategies.